Production of slow protonium in vacuum - Dirk van der Werf (Hyperfine Interactions, 2006)
We describe how protonium, the quasi-stable antiproton-proton bound system, has been synthesized following the interaction of antiprotons with the molecular ion H2+ in a nested Penning trap environment. From a careful analysis of the spatial distributions of antiproton annihilation events in the ATHENA experiment, evidence is presented for protonium production with sub-eV kinetic energies in states around n = 70, with low angular momenta. This work provides a new two-body system for studies using laser spectroscopic techniques.